Creating idiometric short-form measures of cognitive appraisal: balancing theory and pragmatics. - Schwartz, Carolyn E.; Stark, Roland B.; Rapkin, Bruce D. (Tufts University. Tisch Library., 2021)
Keywords: Appraisal, Response shift, Individual differences, Cognitive, Measurement, Idiometric.; Springer Open.